Assessment of Educational Inhaler Technique Interventions Among Community Pharmacists: A Systematic Review - Hussain FN; Paravattil B (Dove Medical Press, 2020)
Farhat Naz Hussain, Bridget Paravattil College of Pharmacy, QU Health, Qatar University, Doha, QatarCorrespondence: Farhat Naz HussainCollege of Pharmacy, QU Health, Qatar University, PO Box 2713, Doha, QatarTel +974 4403 5573Email fhussain@qu.edu.qaObjective: Community pharmacists are the last point of contact before patients are provided with an inhaled asthma device and are expected to adequately educate and train patients on its use. Evidence has shown that pharmacists lack the knowledge and skills required to appropriately counsel patients on these devices. The aim of this systematic review was to focus on evaluating the effects of educational interventions on community pharmacists knowledge of inhaler technique.Methods: A literature search was conducted using the databases Pubmed and Embase with no applied time restrictions. The databases were searched from inception to December 2018. Articles were eligible for inclusion if they reported outcomes evaluating the improvement in pharmacists knowledge of inhaler technique after an educational intervention and provided details of the intervention. Pharmacists working in settings other than community pharmacies and inhaler devices used for conditions other than asthma were excluded.Results: Five studies met the eligibility criteria. Workshops and one-on-one instruction were the main educational strategies used in these studies to augment the pharmacists knowledge of asthma inhaler devices. A checklist was utilized by all studies to evaluate the pharmacists improvement of inhaler technique after an educational intervention. All studies showed an improvement in inhaler technique of pharmacists post-intervention.Conclusion: Studies identified in this systematic review have shown that an educational intervention produced positive outcomes related to the pharmacists knowledge on the steps involved in using asthma inhaler devices. However, the study findings focused on short-term retention of knowledge of inhaler technique and did not address the application of these results in clinical practice.Keywords: asthma, inhaler technique, educational activity, community pharmacy